Utilizing palm oil mill effluent (POME) for the immobilization of Aspergillus oryzae whole‐cell lipase strains for biodiesel synthesis. (26th February 2021) - Rachmadona, Nova; Quayson, Emmanuel; Amoah, Jerome; Alfaro‐Sayes, Daniel A; Hama, Shinji; Aznury, Martha; Kondo, Akihiko; Ogino, Chiaki
Abstract: Palm oil mill effluent (POME) is a palm industrial waste by‐product that is readily available and possesses high quantities of the organic compounds that are necessary for microbial growth. This study investigated the potential of immobilized Aspergillus oryzae whole cells expressing Candida antartica lipase B (r‐CALB) when using a POME‐based medium as a low‐cost carbon source within biomass support particles. The dry cell weight, hydrolytic activity, and remaining protein were measured for a variety of POME (0–2% w/v) and carbon source concentrations (0–2% w/v) with an incubation time of 96 h. Using POME in the culture medium as a carbon source instead of glucose doubled the retention of cell weight from 1.16 ± 0.03 to 2.36 ± 0.02 g within the biomass support particles and improved the hydrolytic activity from 1.61 ± 0.02 to 2.23 ± 0.02 U mg −1 in whole‐cell lipase. This immobilized r‐CALB was used as a catalyst to esterify POME into biodiesel. This synthesis produced an ester content of 97.52 ± 0.21% w/w after 96 h. Immobilized r‐CALB was reusable for more than ten batches, and resulted in an ethyl ester content of more than 90% w/w even after 10 cycles. The present study demonstrated that POME could serve as a sustainable carbon source for industrial microbial culture with the additional incentive of being a treatment that is inexpensive and sustainable. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd